2016
DOI: 10.1371/journal.ppat.1005889
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Composition and Function Drives Wound-Healing Impairment in the Female Genital Tract

Abstract: The mechanism(s) by which bacterial communities impact susceptibility to infectious diseases, such as HIV, and maintain female genital tract (FGT) health are poorly understood. Evaluation of FGT bacteria has predominantly been limited to studies of species abundance, but not bacterial function. We therefore sought to examine the relationship of bacterial community composition and function with mucosal epithelial barrier health in the context of bacterial vaginosis (BV) using metaproteomic, metagenomic, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
122
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 42 publications
9
122
0
1
Order By: Relevance
“…This TFV metabolism can happen quite rapidly and research has shown reduced tenofovir-diphosphate (TFV-DP, the active form of TFV) levels in cervical tissue within two hours and depleted TFV concentrations in cervicovaginal fluid and plasma after one week when high concentrations of Gardnerella vaginalis are present (13 ■■ ,33 ■■ ). CAPRISA-004 participants with non- Lactobacillus dominant microbiota also had enhanced cellular membrane transport protein expression, which could have provided another mechanism for rapid TFV metabolism in cervicovaginal tissue for individuals using gel-based PrEP (34 ■■ ). …”
Section: Text Of Reviewmentioning
confidence: 99%
“…This TFV metabolism can happen quite rapidly and research has shown reduced tenofovir-diphosphate (TFV-DP, the active form of TFV) levels in cervical tissue within two hours and depleted TFV concentrations in cervicovaginal fluid and plasma after one week when high concentrations of Gardnerella vaginalis are present (13 ■■ ,33 ■■ ). CAPRISA-004 participants with non- Lactobacillus dominant microbiota also had enhanced cellular membrane transport protein expression, which could have provided another mechanism for rapid TFV metabolism in cervicovaginal tissue for individuals using gel-based PrEP (34 ■■ ). …”
Section: Text Of Reviewmentioning
confidence: 99%
“… further showed that suppression of inflammation prior to SIV inoculation prevented SIV infection. In addition to recruiting target cells to the site of transmission, there is evidence showing that pro‐inflammatory cytokines facilitate HIV transmission by reducing the integrity of the epithelial barrier in the female genital tract and directly promoting HIV replication through NF‐kB activation .…”
Section: Introductionmentioning
confidence: 99%
“…25 Furthermore, the integrity of epithelial cells isolated from the female genital tract was directly disrupted by the presence of HIV-1. 27 Re-epithelialization, the migration and proliferation of epithelial cells, 28 is an important step of mucosal wound repair, as well as that of skin and other tissues, sealing the epithelial defect and restoring barrier integrity. 27 Re-epithelialization, the migration and proliferation of epithelial cells, 28 is an important step of mucosal wound repair, as well as that of skin and other tissues, sealing the epithelial defect and restoring barrier integrity.…”
mentioning
confidence: 99%